2017
DOI: 10.1016/j.cub.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

The Function and Organization of the Motor System Controlling Flight Maneuvers in Flies

Abstract: Highlights d Flies steer using four muscle groups that insert on tiny parts of the wing hinge d Each muscle group consists of both steadily and transiently active muscles d A stabilizing visual pathway preferentially recruits the steadily active muscles d A pathway for random turns preferentially recruits the transiently active muscles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 55 publications
9
136
0
Order By: Relevance
“…Our data are consistent with a simple summation of the signals of the optomotor and the AX pathway. A recent study of the steering motor system indicates that direct flight muscles are divided into two groups: tonic muscles that are responsible for maintaining the trim of the flight motor and phasic muscles that are primarily recruited during the largest spontaneous turns [19]. We thus predict that the AX neuron makes particularly strong connections with phasic muscle motor neurons.…”
Section: Discussionmentioning
confidence: 92%
“…Our data are consistent with a simple summation of the signals of the optomotor and the AX pathway. A recent study of the steering motor system indicates that direct flight muscles are divided into two groups: tonic muscles that are responsible for maintaining the trim of the flight motor and phasic muscles that are primarily recruited during the largest spontaneous turns [19]. We thus predict that the AX neuron makes particularly strong connections with phasic muscle motor neurons.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the motion of internal sclerites, these techniques also allow visualization of the direct steering muscles during flight (Walker et al, 2014). In parallel, recent breakthroughs in Drosophila genetics also show great promise in revealing the role of specific direct steering muscles both individually and in combination with other muscles in different behaviors (Shirangi et al, 2013;Lindsay et al, 2017).…”
Section: The Wing Hinge Translates Muscle Contraction Into Wing Motionmentioning
confidence: 98%
“…Recent work on Drosophila using genetically encoded calcium reporters (GCaMP6f) in active muscles has revealed some very interesting aspects about the organization of steering muscles at the base of the wing hinge sclerites. The steering muscles in Drosophila are organized into two groups that are anatomically and functionally separated into the larger phasically activated muscles that control the major alteration in wing motion during distinct maneuvers, and the smaller tonic muscles that control the subtler modulations of wing motion (Lindsay et al, 2017). The transmission of strain from the indirect flight muscles, via hinge sclerites to the wings, may be described using a four-bar linkage model which includes the parascutal shelf, Ax1, Ax2 and the wing vein (e.g.…”
Section: The Wing Hinge Translates Muscle Contraction Into Wing Motionmentioning
confidence: 99%
“…We used wide-field fluorescence imaging of muscle calcium signals with GCamp6f (Chen et al, 2013;Lindsay et al, 2017) to map the spatial organization of motor units in the fly femur during spontaneous tibia movements (Figures 1C and S1; Movie S1). We observed that spatial patterns of calcium activity were different for different movements (e.g., tibia flexion vs. extension).…”
Section: Organization and Recruitment Of Motor Units Controlling The mentioning
confidence: 99%